Preference in Cellular Service Providers in the Post Liberalization Era - Revathy, S.; Padmavathy, S. (Indian Journal of Marketing, 2005)
The emergence of marketing concept in respect of services is a recent phenomenon. Let’s produce, what the producer thinks; the market wants, the sales department will manage to sell. This was the focus prior to the beginning of the marketing concept in the context of selling the services. The end of the decade 1950’ spaved avenues for service marketing as users’ satisfaction received due weightage. It is very difficult to predict and understand users behavior obviously it becomes important for every service sector to concentrate on users and their behavior.